2018
DOI: 10.1111/jav.01723
|View full text |Cite
|
Sign up to set email alerts
|

Extensive gene flow along the urban–rural gradient in a migratory colonial bird

Abstract: Urban colonization by wildlife involves a combination of several different mechanisms, including phenotype or genotype sorting, phenotypic plasticity and microevolutionary adaptation. Combination of these processes can produce a rapid phenotypic, but also genetic divergence of urban versus rural populations. Here, we examined the pattern of genetic differentiation between urban and rural populations of a colonial migratory bird, the black‐headed gull Chroicocephalus ridibundus. To this end, we sampled ca 170 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…In turn, analyzes of microsatellite data conducted by Brewer et al 19 revealed that the level of urbanization did not affect genetic diversity and genetic structure of song sparrows inhabiting patches in a gradient of urbanization around Blacksburg (USA), where pairwise F ST values ranged from 0.011 to 0.023. Similar conclusion was provided by studies on black headed gulls Chroicocephalus ridibundus in northern Poland 15 and on common kestrels Falco tinnuculus in Czech Republic 24 , where urban and rural populations did not differ genetically.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In turn, analyzes of microsatellite data conducted by Brewer et al 19 revealed that the level of urbanization did not affect genetic diversity and genetic structure of song sparrows inhabiting patches in a gradient of urbanization around Blacksburg (USA), where pairwise F ST values ranged from 0.011 to 0.023. Similar conclusion was provided by studies on black headed gulls Chroicocephalus ridibundus in northern Poland 15 and on common kestrels Falco tinnuculus in Czech Republic 24 , where urban and rural populations did not differ genetically.…”
Section: Discussionsupporting
confidence: 81%
“…Evaluation of genetic divergence between populations of each species was conducted by calculation of Wright’s fixation index F ST . This is a classic measure of population divergence, although it is known to diminish the role of mutations in inducing genetic variation within populations 15 , 63 . Therefore, an alternative statistic R ST 63 was introduced based on the stepwise mutation model, which can more accurately reflect changes in microsatellite allele sizes 21 .…”
Section: Methodsmentioning
confidence: 99%
“…In other words, the urban environment has filtered birds based on their inherent levels of tolerance in a similar way regardless of variation in human levels. Indeed, based on genetic studies, in some species, rural populations are a source of individuals to urban populations [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015–2016, 330–350 pairs of black-headed gulls bred in the Bydg-IND colony, 120 pairs in Bydg-REC and 880–1200 pairs in Kusowo. The extent of anthropogenic pressure, physiographic characteristics of the areas surrounding the breeding sites and detailed information about the study area were described by Kitowski et al ( 2017 ) and Indykiewicz et al ( 2018a ).…”
Section: Methodsmentioning
confidence: 99%